Legal status of diplomatic workers: rights, state guarantees, encouragement - T. A. Zanko (Vestnik MGIMO-Universiteta)
This article provides an analysis of the legal status of diplomats in the Russian Federation with regard to their rights, safeguards and rewards. These elements are presented through the prism of comparative research of more than a dozen countries and consider the experience of diplomatic service legal regulation in the former Soviet Union countries as well as in other foreign countries.